Enhanced Thermoelectric Performance of n‐Type Organic Semiconductor via Electric Field Modulated Photo‐Thermoelectric Effect. Issue 31 (24th June 2020) - Zhao, Wenrui; Zhang, Fengjiao; Dai, Xiaojuan; Jin, Wenlong; Xiang, Lanyi; Ding, Jiamin; Wang, Xian; Wan, Yan; Shen, Hongguang; He, Zihan; Wang, Juan; Gao, Xike; et al.
Abstract: Modulating photophysical processes is a fundamental way for tuning performance of many organic devices. However, it has not been explored as an effective strategy to manipulate the thermoelectric (TE) conversion of organic semiconductors (OSCs) owing to their critical requirement to carrier concentration (>10 18 cm −3 ) and the fact of low exciton separation efficiency in single element OSCs. Here, an electric field modulated photo‐thermoelectric (P‐TE) effect in an n‐type OSC is demonstrated to realize a significant improvement of TE performance. The electrical and spectroscopy characterizations reveal that the electric field gating generates combined modulation of exciton separation, charge screening, and carrier recombination, which produces a more than ten times improvement of photoinduced carrier concentration. These coupled processes contribute to the unconventional Seebeck coefficient ( S )‐electrical conductivity (σ) trade‐off relationship of the photoexcited films, therefore leading to a more than 500% enhancement in the power factor for n‐type OTE semiconductors. This work opens a unique way toward state‐of‐the‐art organic P‐TE materials for energy harvesting applications. Abstract : An electric field is demonstrated to enhance the photo‐thermoelectric effect by promoting the exciton separation efficiency with a coupled modulation process. The increased photoinduced carrier concentration and abnormal trade‐off relationship of the thermoelectric parameters together lead to an enhancement in the power factor of more than 500% to 11.2 μW m −1 K −2 .